Pencabutan Hak Politik Mantan Terpidana Kasus Korupsi Berdasarkan Perspektif Hak Asasi Manusia - Celia Santa Katarina (Darma Cendika Catholic University, 2019)
This study describes the deprivation of political rights of convicted corruption in the human rights perspective. This research is motivated by the discourse to revoke the political rights of convicted corruption on a regular basis. The discourse arises because of the many former corruption convicts who nominated themselves to be the people's representatives in the 2019 elections. In addition, the discourse arose because of the weakening of people's trust in their representatives, it was triggered by the failure to fulfill the objectives of criminal justice and the criminal justice system in Indonesia. But the discourse about revocation of political rights in an indisputable manner is not without rejection. Various parties claim that revoking political rights against convicted corruption is a human rights violation and therefore should not be done. This research has the formulation of the problem, among others, how the concept of revocation of political rights in Indonesia and how revocation of political rights against convicted of corruption in terms of human rights. To answer these problems, the statute approach and conceptual approach are used. The results of this study indicate that Indonesia has the concept of revoking political rights as regulated in Articles 35 and 38 of the Criminal Code but is not strong enough to fulfill the criminal purpose and therefore must be changed, and the revocation of political rights is not a form of discrimination against human rights.